Do we need a shared European MOOC platform - Santos, Tiago; Costa, Carlos; Aparicio, M. (Position papers for European cooperation on MOOCs, 2015)
In the last few years, Massive Open Online Courses (MOOCs) have dominated the discussion of the role of online learning in the future of higher education (HE). The MOOC movement is mostly based in the USA where the for-profit educational start-ups such as Coursera, Udacity, and the MIT and Harvard-founded non-profit platform edX take the lead. On the European level, many Member States have recognized the potential impact of technology on education and e-learning initiatives have been launched. Some universities have joined the USA initiatives and others were created, like the pan-European initiative OpenupEd, supported by the European Commission (EC), as well as FutureLearn, Iversity, France Université Numérique (FUN), UNEDcoma or Miríada X. Nonetheless, European initiatives have been isolated and fragmented and the EU risks in lagging behind the USA and some Asian countries that are investing in ICT-based strategies to reshape education and training. The EU recognizes that has a role to play in the promotion of best practices and support exchanges across Member States. The EU intervention concerning the deployment and availability of digital technology and content through financial support, public-private partnerships and recommendations, could generate economies of scale and interoperability benefits, thus avoiding fragmentation. One solution that fits this line of action would be the creation of a shared European MOOC platform, where HE institutions (HEI) could publish their courses. Such platform would enable the collaboration of (pan-)European HEI in the development of new educational solutions which could otherwise be out of reach if designed by each institution on its own, promoting their international reach, including recruitment and support.